PERAN CAMAT DALAM PELAKSANAAN PEMBANGUNAN DI KECAMATAN SEBERANG ULU 1 KOTA PALEMBANG - Nifi Lamingthon (Jurnal Pemerintahan dan Politik, 2019)
The development plan in the Sub-District Government apparatus by the Sub often doesn't run as expected. The participation of all parties in the development of the area of the district is absolutely decisive, because after all the potential area that owned if less grasp implementation alignment apparatus development, sub-district development goals by itself will not be achieved as expected. The subdistrict is part of local governance which he supervises several wards and is headed by a Head, has a duty as executor cantonal techniques that have a specific work area and also has a function.Keywords: Head, development, Good Government